Evaluation of the Religious Friday Program in the Formation of Religious Character in UIN Raden Fatah Palembang Students (Case Study of the Faculty of Tarbiyah and Teacher Training) - Adinda, Desva; Idi, Abdullah; Fauzi, Muhammad (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Program evaluation is a series of activities that are carried out deliberately to see the success rate of a program, conducting a program evaluation is an activity that is intended to find out how high the success of the planned activities is (Kurniawati 2021). Meanwhile, according to Cronbach and Stufflebeam, program evaluation is an effort to provide information to be conveyed to decision-makers. The methods used in this study are observations on the religious Friday program, interviews with the Head of the Islamic Religious Education Study Program, staff/lecturers and students who participate in the religious Friday program, documentation related to the evaluation of the religious Friday program in the formation of religious character. The results in this study include the program evaluation model used by the researcher is the CIPP evaluation model. CIPP stands for Context Evaluation, Input Evaluation, Process Evaluation, Product Evaluation.